Performance and potential energy saving of thermal dryer with intermittent impinging jet - Kurnia, J.C. (Elsevier Ltd, 2017)
In designing an energy efficient impinging jet dryer, it is essential to match the energy demand for drying with the supply of heat by convection to avoid overheating and energy wastage. One way to achieve this is by intermittently supply heat to the drying chamber. By using computational fluid dynamics (CFD) approach, this study numerically investigates the possibility of energy saving by intermittency. First, inlet temperature intermittency is applied. This is conducted by alternately raise it to drying temperature and lowers it to the ambient temperature at certain period. Second, inlet velocity intermittency is applied which is conducted by alternately supplying the hot air to the several drying chamber. One, two, three and four chamber configurations are evaluated. In addition, the intermittency period of 10, 20 and 30 min were examined. The results reveal that the steady impinging jet offers faster drying rate as compared to intermittent impinging jet drying under the same inlet conditions. In addition it was found that drying rate goes down as the number of drying chamber increases. However, the intermittent impinging jet drying offers advantages in term of temperature uniformity and energy conservation. For the same energy usage, the production rate of single drying configuration is only one fourth of the four chamber configuration. This indicates the potential of multi chamber configuration in a real drying application. © 2016 Elsevier Ltd